2020
DOI: 10.1530/eje-20-0609
|View full text |Cite
|
Sign up to set email alerts
|

Variation in sensitivity and rate of change in body composition: steps toward individualizing transgender care

Abstract: Objective Transgender individuals sometimes report a lack of physical change during hormone treatment, such as alterations in muscle tone or fat distribution. Identifying characteristics of this subgroup could be a step towards individualizing hormone therapy in transgender individuals. Therefore, we study the variation of changes in body composition and characteristics associated with a lack of change. Design and methods: Body composition measures were recorded in 323 transmen and 288 transwomen at every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Estradiol concentrations were also not associated with these outcomes. This is in line with previous studies in trans women, which found no association between estradiol concentrations or administration route and change in fat percentage or breast development ( 3 , 19 , 34 ). Our results are in contrast with other studies suggesting that high estrone levels can act as an estrogen antagonist ( 14 , 35-37 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Estradiol concentrations were also not associated with these outcomes. This is in line with previous studies in trans women, which found no association between estradiol concentrations or administration route and change in fat percentage or breast development ( 3 , 19 , 34 ). Our results are in contrast with other studies suggesting that high estrone levels can act as an estrogen antagonist ( 14 , 35-37 ).…”
Section: Discussionsupporting
confidence: 93%
“…The machine output of fat percentages was used. A more detailed description of the bioelectrical impedance analysis protocol is described elsewhere ( 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, body composition did change, fat percentage decreased (−4%) and lean mass increased (+1.6%), also resulting in increased handgrip strength [61]. A lack of changes with GAHT in body composition was examined in ENIGI [62]; in 323 trans men (mean age = 21), a lack of change after 24 months of GAHT was observed in 20.2%. Low mean testosterone and high mean luteinizing hormone (LH) levels were associated with no change in this group.…”
Section: Body Composition and Contoursmentioning
confidence: 99%
“…Body mass index (BMI) appeared to be an important determinant of body composition changes, with lower BMI associated with greater modifications [ 10 ]. Furthermore, in trans AFAB people, lower T and higher luteinizing hormone levels showed an association with a lack of body composition changes [ 11 ].…”
Section: Overview Of Acquired Knowledgementioning
confidence: 99%